2001
DOI: 10.1128/aac.45.7.2173-2176.2001
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Cat Model for Predicting Human Nucleoside Analogue Pharmacokinetics in Blood and Seminal Plasma

Abstract: To establish whether a feline model can predict nucleoside analogue behavior in human semen, zidovudine (ZDV) and lamivudine (3TC) pharmacokinetic parameters (PKs) were determined in the blood and seminal plasma of healthy cats. Our results show considerable similarity in ZDV and 3TC PKs between cats and humans. As in humans, ZDV and 3TC tend to accumulate in feline seminal plasma. Area under the blood plasma concentration-time curve was predictive of seminal plasma excretion. The felid model offers a unique i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…[5][6][7][8][9] However, fewer of the antiviral compounds have been studied in cats. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][46][47][48][49][50][51] Information on the clinical use and dosing of zidovudine in cats is varied and contradictory. Anecdotal information supports the use of zidovudine (5 to 15 mg/kg, PO, q 12 h) for neurologic manifestations of natural FIV infection in cats.…”
Section: Administration Routementioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] However, fewer of the antiviral compounds have been studied in cats. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][46][47][48][49][50][51] Information on the clinical use and dosing of zidovudine in cats is varied and contradictory. Anecdotal information supports the use of zidovudine (5 to 15 mg/kg, PO, q 12 h) for neurologic manifestations of natural FIV infection in cats.…”
Section: Administration Routementioning
confidence: 99%
“…5,9 These results indicate that zidovudine is a potent inhibitor of FIV in vitro.Despite the use of zidovudine in several clinical 10-12 and experimental 7,13-15 studies in FIV-infected cats and in experimental studies in FeLV-infected cats, [16][17][18][19] information on the pharmacokinetics of zidovudine in cats is scarce. [20][21][22] The pharmacokinetics of zidovudine have been well documented in mice, 23 rats, 24 monkeys, 25 and humans. 26,27 The purpose of the study reported here…”
mentioning
confidence: 99%